Service model based on standardized work and supplier management to increase the nps in a sme in the restaurant sector - Morales Quevedo, Luis Ernesto (2024)
The growing boom of global gastronomy has been manifested in Lima with a significant increase in maki restaurants. Despite this growth, customer satisfaction, a key factor for success, presents challenges. In the particular case of a restaurant, the problem lies in a Net Promoter Score (NPS) of -2%, considerably lower than the industry average (60%). This discrepancy, mainly motivated by the quality of the food, poses the challenge of raising the NPS to the 60% standard. To address this challenge, a two-pronged approach is proposed: standardized work and supplier management. The first ensures consistent processes that guarantee quality consistency, while the second ensures the excellence of the ingredients used. The validation of this approach was carried out through a pilot test, based on surveys of 385 customers. The implementation of the model yielded significant improvements: an increase in NPS to 62.5%, thus surpassing the industry average. Additionally, the restaurant achieved a Customer Satisfaction Score of 75% for food quality and 81% for waiting time. These results demonstrate the effectiveness of the model and its techniques, showcasing its ability to solve the identified problem and improve customer satisfaction.